The Transformative Power of Urban Arrival Infrastructures. Berlin’s Refugio and Dong Xuan Center. - Kreichauf, René; Rosenberger, Olivia; Strobel, Paul (Cogitatio Press, 2020)
Migration researchers and urban scholars are increasingly applying infrastructural approaches to analyze the production and organization of urban spaces and migration. While transformative and transforming power seem to be inherent characteristics of infrastructures, studies to date have rarely emphasized this aspect, only placing minimal focus on its importance for understanding the constitution and development of infrastructures and for examining the mobility of migrants. In the current article, we study Berlin’s Refugio, an alternative form of housing for forced migrants, and the city’s Dong Xuan Center (DXC), a Vietnamese hypermarket. We argue that they not only represent infrastructures in which newcomers reach a city, and navigate their trajectories, as well as the obstacles, and opportunities of urban life, but they are also ‘infrastructures of conversion’ that transform material space and the people inhabiting them, and their entanglement with the city. While the DXC and Refugio emerged out of necessity, addressing the lack of economic (DXC) and housing (Refugio) opportunities, they have changed into cultural and economic hubs for migrant communities and beyond. On the one hand, these changes come with multilayered negotiation processes, revealing a complex interplay of interests, actors, and internal hierarchies within the DXC and Refugio. On the other hand, their transformation illustrates the influence of local planning authorities, institutions, and the pressure to culturally and economically exploit their social, spatial, and ‘ethnic’ characteristics. This mesh elucidates the diffuse position of both infrastructures in the urban realm. While their existence and future development is constantly challenged, they simultaneously represent political spaces that prompt institutional logics and questions of immigrant integration.
Keywords: Großstadt; Einwanderung; Migration; Stadtraum; Soziale Integration; Wohnprojekt; Gemeinschaftseinrichtung; Supermarkt; Sozialinfrastruktur